Sweet Potato New Varieties Screening Based on Morphology, Pulp Color, Proximal Composition, and Total Dietary Fiber Content via Factor Analysis and Principal Component Analysis - Leite, Cláudio Eduardo Cartabiano; Souza, Brunna de Kácia Ferreira; Manfio, Candida Elisa; Wamser, Gerson Henrique; Alves, Daniel Pedrosa; de Francisco, Alicia (Frontiers in Plant Science, 2022)
A sample set of eighteen sweet potatoes (Ipomoea batatas (L.) Lam) segmented into six registered cultivars and twelve new varieties were evaluated. The 142 tuberous roots were obtained from a sweet potato germplasm bank (BAG-sweet potato; -27.417713768824555, -49.64874168439556), from plants belonging to a sweet potato breeding program. All samples were characterized according to their morphology, instrumental pulp color, proximate composition and total dietary fiber. The analytical results were submitted to parametric and non-parametric statistical tests for sample variance data comparison. Moreover, the screening of the cultivars and new varieties was performed by exploratory statistical analysis, Factor Analysis and Principal Component Analysis. From the sixteen independent variables that characterized the samples, the exploratory Factor Analysis identified thirteen that had a communality greater than 0.7, with 92.08% of assertiveness. The Principal Component Analysis generated 4 principal components able to account for 84.01% of the explanatory variance. So, among the six registered cultivars SCS372 Marina and SCS370 Luiza showed the capability to be employed as cultivars for production. Among the twelve sweet potato new varieties, samples 17025-13, 17125-10, and 17117 met the requirements for patent and registration. These results will be useful to farmers who wish to use these sweet potatoes in the development of their crops.